Electrochemistry of N4 Macrocyclic Metal Complexes Volume 2: Biomimesis, Electroanalysis and Electrosynthesis of MN4 Metal Complexes - Zagal, Jose H.; Bedioui, Fethi (Springer International Publishing : Imprint: Springer, 2016)
This new edition describes the state of the art regarding metal complexes of N4-ligands, such as porphyrins and phthalocyanines. Volume 2 focuses on the electro assisted use of N4 complexes as biomimetic models for studying several biological redox processes. It focuses on molecular oxygen transport and catalytic activation to mimic monooxygenase enzymes of the cytochrome P450 in particular. It also examines N4 complexes' use as catalysts for the oxidative degradation of various types of pollutants (organo-halides, for example) and residual wastes. The remarkable activity of these complexes towards a large number of significantly relevant biological compounds makes them excellent candidates as electrode modifiers for electrochemical sensing. This volume also discusses applications of N4 Macrocyclic Metal Complexes to photoelectrochemistry and photocatalysis, and concludes with an exciting section on Electrosynthesis of N4.